Building business strategies through entrepreneurship competence and product innovation to improve performance - Hariyanti, Hariyanti; Nuryati, Nuryati (Journal of Business & Banking, 2022)
The purpose of the study was to determine and empirically test the relationship between entrepreneurial competence and product innovation on performance through business strategies for PKK women, Banjarsari District, Surakarta City, Central Java, Indonesia. The sample consists of 100 PKK women who have a business or side business of batik patchwork, taken using a purposive random sampling technique. The data were analyzed concerning the Validity and Reliability test, Linearity, t-test, F-test,Â Coefï¬cient of Determination, Path analysis and Correlation. The results of the testÂ partially that product innovation and entrepreneurial competence and business strategyÂ have a positive and signiï¬cant effect on performance. Entrepreneurial competence and product innovation have a positive and signiï¬cant effect on business strategy partly. TheÂ variables of entrepreneurial competence, product innovation and business strategy were able to contribute to improving performance by 78.22%, and the rest is explained by other variables such as entrepreneurial orientations, environment, competitive advantage and others. From the path analysis, it was found that business strategy could better mediate the effect of entrepreneurial competence and product innovation on performance. To improve performance through business strategies it is more effective if by increasing product innovation, after that entrepreneurial competence.